2012
DOI: 10.1002/ange.201107739
|View full text |Cite
|
Sign up to set email alerts
|

An O‐Centered Structure of the Trinuclear Copper Center in the Cys500Ser/Glu506Gln Mutant of CueO and Structural Changes in Low to High X‐Ray Dose Conditions

Abstract: Cu3 in Aktion: Die O‐zentrierte Struktur des dreikernigen Kupferzentrums in der Multikupferoxidase CueO wurde als Intermediat der Vier‐Elektronen‐Reduktion von Disauerstoff charakterisiert (siehe Bild). Die Struktur wurde durch In‐situ‐Datensammlung für Röntgendiffraktogramme und Kupfer‐K‐Kanten‐Spektren bei schwacher bis starker Röntgenbestrahlung ermittelt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…This can now be done rather routinely at synchrotron sites, especially using online optical microspectrophotometry 20 as well as by X-ray absorption spectroscopy. 28 Protein crystals are typically grown aerobically and thus maintain the oxidized state of their metal ion sites. X-rays have been found to cause reduction of the protein's redox site, notably a metal ion, primarily because this is the thermodynamically favored site of reduction 29 by the primary irradiation produced hydrated electrons and secondary reducing radicals.…”
Section: Ra D I a Ti On In D U Ce D C Ha N Ge S Wi Th In R Ed Ox P mentioning
confidence: 99%
“…This can now be done rather routinely at synchrotron sites, especially using online optical microspectrophotometry 20 as well as by X-ray absorption spectroscopy. 28 Protein crystals are typically grown aerobically and thus maintain the oxidized state of their metal ion sites. X-rays have been found to cause reduction of the protein's redox site, notably a metal ion, primarily because this is the thermodynamically favored site of reduction 29 by the primary irradiation produced hydrated electrons and secondary reducing radicals.…”
Section: Ra D I a Ti On In D U Ce D C Ha N Ge S Wi Th In R Ed Ox P mentioning
confidence: 99%
“…A recent crystallographic study on a double mutant Cys500Ser/Glu506Gln showed that the hydrogen bond network leading from the exterior of the protein molecule to TNC formed with the amide group in the side chain of the Gln residue [14]. However, the carboxyl group of the side chain of Glu is distinct from the amide group in the side chain of Gln which does not cycle between the protonated and deprotonated forms [7].…”
Section: Reduction Of O 2 To 2h 2 Omentioning
confidence: 99%
“…The mutations of Glu506 with Asp, Ala, and Ile were performed to impose a variety perturbations on the hydrogen bond network, and to compare the results with data obtained from the previous Gln mutation which inactivates the hydrogen bond network with respect to proton transfer [6,7,14]. We expect that the hydrogen bond network is modified, but still highly functional in the Glu506Asp mutant.…”
Section: Introductionmentioning
confidence: 99%
“…1) [11,[19][20][21]. Cycling of protonation and deprotonation in the side chain of the conserved Glu residue coupled with the change in redox state of BOD and CueO has been observed by FT-IR studies [22].…”
Section: Introductionmentioning
confidence: 99%
“…Cycling of protonation and deprotonation in the side chain of the conserved Glu residue coupled with the change in redox state of BOD and CueO has been observed by FT-IR studies [22]. Mutations on the conserved Glu residue have been performed for CueO and Fe3p, resulting in the successful trapping and characterization of the intermediate II [11,19,21]. Mutations of this Glu residue with Gln led to practically complete loss in enzymatic activities, but its substitution with Ala exhibited considerably high enzymatic activities due to a formation of compensatory hydrogen bond network with only water molecules [19,23,24], while it was found that Asp located in one of other two channels leading to TNC also concerns profoundly in the formation of water molecules [25,26].…”
Section: Introductionmentioning
confidence: 99%